2018
DOI: 10.1016/j.cub.2018.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-Gatherers Maintain Assortativity in Cooperation despite High Levels of Residential Change and Mixing

Abstract: Highlights d Assortment on cooperation is a characteristic feature of hunter-gatherer life d Assortment persists despite substantial migration and residential mixing d No evidence for stable social types or a preference to live with cooperators d Individuals respond in kind to the cooperative behavior of their group members

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 43 publications
3
56
2
Order By: Relevance
“…Second, there is no evidence for stable variation in generous dispositions in small-scale societies. In longitudinal data among the Hadza, contributions to a public good game were not predicted by previous contributions, but rather the contributions of an individual's campmates (Smith, Larroucau, Mabulla, & Apicella, 2018).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Second, there is no evidence for stable variation in generous dispositions in small-scale societies. In longitudinal data among the Hadza, contributions to a public good game were not predicted by previous contributions, but rather the contributions of an individual's campmates (Smith, Larroucau, Mabulla, & Apicella, 2018).…”
mentioning
confidence: 77%
“…Data measuring morally-relevant behavior, such as generosity, further suggest a lack of stable variation in moral dispositions in the Hadza and other non-WEIRD populations. In a longitudinal study, a Hadza's previous generosity in an economic game did not predict their subsequent contributions, and instead the only significant predictor was how much his or her campmates contribute (Smith et al, 2018). And in a small study (n = 12) of the Tsimané of Bolivia, generosity in a dictator game in one year did not predict generosity in a later year (Gurven, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models of evolutionary dynamics suggest that evolution may favor cooperative types when partner choice is feasible ( Eshel and Cavalli-Sforza, 1982 ; McNamara et al., 2008 ; Stanley et al., 1993 ), and evidence from Hadza foragers (and other groups) suggests that people are strongly influenced in their cooperation behavior by the norms of the groups to which they belong ( Smith et al., 2018 ). By endowing actors with the tendency to manipulate the ties around themselves, bots (and people) may be able to affect the cooperativity of their groups, creating a convivial local environment for cooperative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although many cultural traits possess a phylogenetic signal, suggesting long-term cultural stability (Mathew and Perreault 2015), other traits relating to cooperation, such as food-sharing, show little phylogenetic signal (Ringen et al 2019). Studies on forager cooperation have shown that cooperative behaviour is variable within ethnographic groups (Smith et al 2018), often based on differences in ecology (Lamba and Mace 2011;Smith et al 2016), and changeable within the space of a single generation (Gurven et al 2002). These findings are consistent with this lack of phylogenetic signal and suggest that cooperative behaviour can display a rapid adaptive response to changing environments.…”
Section: Do Group Differences Arise Via Stochastic Processes and Are mentioning
confidence: 99%